PERANAN GOOD CORPORATE GOVERNANCE DALAM MEMPREDIKSI FINANCIAL DISTRESS - Diah Mentari Cahyani; Ni Nyoman Ayu Diantini (Faculty of Economics and Business Udayana University, 2016)
This study aims to find the effect of job involvement and organizational justice on three types of organizationalcommitment, which are affective, continuance and normative. This research was conducted in Pacto-Bali, using 70 employees as its respondents. Sampling technique used in this study was saturated sampling technique.Data was collected through interviews and questionnaires. The data analysis technique was multiple linear regression, which was processed using SPSS software.The findings indicate that job involvement has positiveinfluence on each types of organizational commitment, that was affective commitment, continuance commitment and normative commitment. The same finding was found in the relationship between organizational justiceand organizational commitment, where the more justice the employees received the more committed the employees to the organization. To improve the organizational commitment of employees, Pacto-Bali shouldincrease employee motivation by inviting employees to involve in the decision making process, and also should improve the networking between the owners and employees in order to help organization to reach its goals.